Analysis of Alimony Provision for Former Wives in the Case Study of Tangerang District Court Decision Number: 927/PDT. G/2017/PN. TNG - Widodo, Ragil; Kurniawan, Wahyu Nandang; Al Hakim, Ahmad Faruq (The Digest: Journal of Jurisprudence and Legisprudence, 2022)
The allocation of post-divorce financial support to the ex-wife presents an intriguing topic, exemplified in the Tangerang District Court Decision Number: 927/Pdt.G/2017/PN.Tng, a case involving civil disputes arising from a divorce. The court ruled that the Reconviction Defendant/Convention Plaintiff must provide a monthly allowance of Rp. 17,500,000,- (seventeen million five hundred thousand rupiah) to the Reconviction Plaintiff/Convention Defendant until the latter remarries. Employing normative research methods with a normative juridical approach, the author observes that the judge, while referencing Article 41 of Law No.1 of 1974, failed to provide any legal reasoning in the judgment. This lack of legal reasoning suggests the panel lacked a sound legal basis, undermining the application of Article 41(c) of Law No.1 of 1974 regarding Marriage, which is non-imperative. Therefore, the importance of prudence, justice, and a robust legal foundation in rendering decisions is highlighted to prevent the issuance of frivolous or ambiguous judgments that could complicate the execution of court decisions.